Psychiatry and Sports Medicine - Gonzalez Hofmann C; Fontana R; 3; Parker T; Deutschmann M; Dewey M; Reinsberger C; Claussen MC; 5; 7; Scherr J; Jeckell AS (Deutsche Zeitschrift für Sportmedizin)
Head injuries are common in competitive and recreational sport. Nomenclature, though inconsistent, identifies mild traumatic brain injury (mTBI) based on acute diagnostic criteria, whereas a sport-related concussion (SRC) is event-related and specific to mTBI experienced while participating in athletic ac- tivity. The effects of SRC are often neurological, neuropsychological and/or psychiatric with a variety of symptoms.Different organizations categorize these symptoms differently and this variance demonstrates that no uniform clinical classification system has been agreed upon. Diagnosis of SRC is based on clinical examination. Numerous symptom checklists and assessments are available for clinical diagnosis, but their validity is somewhat limited. There is increasing awareness regarding the psychiatric deficits associated with SRC and the potential for developing post-concussion syndrome (PCS). In addition to complex, causal SRC-associated symptoms, reactive psychological complaints may also occur, as well as social mistreatment on recovery from SRC.Pre-existing mental health conditions are associated with an increased risk for developing PCS. This often necessitates the implementation of psychiatric or psychotherapeutic care after SRC. As with mTBI and SRC, no standardized classification has been established for PCS. Multi-stage rehabilitation strategies can help injured athletes navigate a successful recovery and prevent premature return to play. Further research on the utility of psychotherapy, psychopharmacotherapy, and exercise therapy of PCS is needed.Key Words: Concussion, Mental Health, Post-Concussion Syndrome, Interdisciplinarity